RESEARCH OF DIELECTRIC LIQUIDS BEHAVIOR IN INTENSE ELECTRIC FIELDS - Trofimov, Іgor; Zubchenko, Alexander; Maximov, Sergey; Kolomiiets, Ganna (Proceedings of National Aviation University, 2013)
There was researched the intense electric fields influence on processes which occur in dielectric liquids and in interelectrode gap, and described study of motion of particles suspended in transformer oil under the electric field action. There was established the electrodes optimal design which allows obtaining the treated liquid quality.